Fluorogenic Fibrinogen and Fibrin Facilitate Macromolecular Assembly and Dynamic Assay of Picomolar Levels of Plasminogen Activators under Well Mixed Conditions - Wu, Jung-He; Diamond, Scott L (Thrombosis and Haemostasis, 1995)
Fibrinogen labeled with fluorescein isothiocyanate (FITC) was tested for its ability to serve as a template for macromolecular assembly as well as to provide a fluorogenic signal to allow continuous monitoring of plasminogen activation and fibrinolysis. As dilute solutions of FITC-fibrinogen or FITC-fibrin fiber suspension were degraded during lysis, release of fluorescent fragments abolished proximity- based quenching and resulted in a 2.0- or 3.6-fold increase in fluorescence intensity, respectively. Addition of plasmin at a final concentration of 10 pM to FITC-fibrinogen (10 nM) produced a detectable level of fluorescence dequenching. The assay had sufficient sensitivity to detect plasmin activity in the presence of excess antiplasmin activity, indicating the dissociation of a reversible antiplasmin-plasmin complex. The detection limit of the reaction assay was 20 pM and 200 pM of recombinant tPA and urokinase, using 10 nM FITC-fibrin and 10 nM and 5 nM plasminogen, respectively. The 10-fold greater sensitivity of the assay for tPA was likely due to the molecular assembly of tPA and plasminogen on the FITC-fibrin. Addition of thrombin (1 U/ml) and plasmin (0.1 nM) to 10 nM FITC-fibrinogen produced fluorescence quenching at first due to fibrinogen polymerization followed by dequenching due to fibrinolysis. Addition of 10 mM ∈-aminocaproic acid to mixtures of thrombin and plasmin allowed the quenching assay of thrombin activity in the presence of active plasmin. FITC-fibrinogen could be copolymerized with recalcified platelet poor plasma (isolated from citrated whole blood) to yield fibrin that was fluorogenic. Dequenching was observed when plasmin was used to degrade the fibrin formed from the platelet poor plasma. Given the large signal generated upon degradation of the fluorogenic fibrin(ogen), at least 105 determinations can be run from 100 mg of FITC-labeled fibrinogen using a standard fluorimeter and 0.1 to 3.0 ml reaction volumes. The versatility of the fluorogenic fibrinogen substrate allowed the configuration of assays to detect and measure the activity of thrombin, plasmin, tPA, uPA, and α2-antiplasmin. The ability to assemble blood proteins on a fluorogenic fibrinogen or fibrin template provides unique opportunities for the dynamic study of binding and enzymatic events on the fibrin surface under well mixed conditions.